ความวิตกกังวล การสนับสนุนทางสังคม และความสามารถในการปฏิบัติหน้าที่ในระยะหลังคลอดของผู้ที่เป็นมารดาครั้งแรก - กัญญาณัฐ สิทธิภา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Maternal functional status during postpartum is an important health outcome for first-time mothers. The purpose of this descriptive correlational research study was to explore anxiety, social support, and postpartum functional status among first-time mothers. The subjects were 102 first-time postpartum mothers during a 6-8 weeks period who received service at Maharaj Nakorn Chiang Mai Hospital or Chiang Mai Health Promotion Hospital, from July to September 2014. The research instruments used were the State Anxiety Inventory Form Y by Spielberger (1983), translated into Thai by Nontasak, Aemsupasit and Thapinta (1995), the Mother Social Support Questionnaire developed by Sitthiboonma, Kantaruksa, and Supavititpatana (2014) and based on the social support concept by House (1981), and the Maternal Functional Status Questionnaire developed by Baosoung, Sansiriphun and Tiansawad (2014). Data were analyzed using descriptive statistics and Pearson's product moment correlation.